Physical abuse and emotional intelligence in children from an educational institution, Huancavelica - Huamán Albites, Margarita Isabel (2020)
Objective. To determine the relationship between physical abuse and emotional intelligence in children from an educational institution in Huancavelica. Methods. Observational, correlational, cross-sectional research; a sample of 48 children, between 10 and 13 years old, was taken; the psychometric technique, the semi-structured interview and the Likert scale were used. Results. The type of physical abuse is evidenced by the use of ear-pulling, hitting with a belt, hitting with the hand or slapping, kicking, hitting with a chicote, stick or rope, pinching and pushing. The mother appeared as the main aggressor, followed by parents and siblings. The abuse was severe by 24%, moderate by 21% and mild by 13%. Girls were the least abused compared to boys. There were no differences by level of abuse, regarding stress management, from adequate to atypical capacity; with regard to the state of mind, the victims of abuse showed a low to poor capacity, being first the moderate one, followed by the severe one and, finally, the mild one. Conclusion. There is a low or non-significant negative relationship (rs = -0.156, p > 0.05) between physical abuse and emotional intelligence, as an adequate to high emotional intelligence is found, regardless of the level of physical abuse.